Zona Netral Dan Akibat Hukum Menurut Hukum Internasional - Aldo Aldo; Josina Augustina Yvonne Wattimena; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The border zone can also be viewed as neutral by the two countries that divide it. The territory of a country refers to the sovereignty, sovereign rights, and control of a country over its territory in real terms.Purposes of the Research: The research method used is normative juridical, namely the approach taken by studying existing library materials. The problem approach used is the law approach, the concept approach, and the case approach. The collection of legal materials through literature study and analyzed using normative qualitative analysis techniques. Methods of the Research: The research method used is normative juridical, namely the approach taken by studying existing library materials. The problem approach used is the law approach, the concept approach, and the case approach. The collection of legal materials through literature study and analyzed using normative qualitative analysis techniques.Results of the Research: This research shows that this zone exists to prevent a ceasefire. Countries in this zone have agreed to limit their influence in the zone. That relations with other members of the international community and regulates everything that happens or occurs outside its territorial boundaries as long as it is related to the interests of that country. Indonesia's land and sea border areas are claimed to have essential values in maintaining state sovereignty, based on Law Number 3 of 2002 concerning National Defense. This is based on Article 2 of the United Nations Charter paragraph (1), which states that international relations are founded on equality and freedom. Relations According to Article 2 paragraph (4), the government may not use force against the territorial integrity or political independence of other countries when conducting international affairs.